Pemanfaatan Sampah Untuk Mengurangi Pemanasan Global Upaya Menuju Pembangunan Berkelanjutan - Setiawan, Andi Arif; Emilia, Ita; Putri, Yunita Panca (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The rapid growth of the industry, on the one hand produces the main product, on the other hand produces by-products in the form of waste or garbage. This waste situation is exacerbated by the accelerating population growth, which results in the production of the waste increasing. This phenomenon is also accompanied by the need for large natural resources, which of course has an impact on the environment Waste is formed as a result of human activities in the use of materials (raw materials) and energy that undergo biological, physical and chemical processes so as to produce main products (desired products) and by-products or those that are not cooled (waste). The impact of waste accumulation is pollution in water, soil and air, in addition to causing global warming. Efforts to reduce the pile of waste by using the principles of reuse, recovery and recycle.